Pengaruh Faktor Geologi dan Perubahan Iklim terhadap Abrasi Pantai di Kabupaten Padang Pariaman - Maulana, Ibnu; Prarikeslan, Widya (Lembaga Yasin AlSys, 2024)
Having a large coastal area and directly facing the Indian Ocean, Indonesia is vulnerable to several disasters, one of which is abrasion. West Sumatra Province loses 56.3 hectares of land per year due to abrasion, including Padang Pariaman.The objectives of this study, (1) Analyzing changes from the coastline in 2003, 2013, and 2023 in Padang Pariaman Regency. (2) Analyzing the influence of geological factors (Lithology, Rock Type, Topography) and climate change (Rainfall, Air Temperature, and Wind Speed) on abrasion events in Padang Pariaman Regency. The analysis method of shoreline changes using the Digital Shoreline Analysis System (DSAS) and the method of analyzing the influence of geological factors and climate change on abrasion using the Scorring method with the help of ArcGIS software and Statistical Product and Service Solution (SPSS) in determining the effect of lithology, rock type, slope, rainfall, air temperature and wind speed on shoreline changes. Based on the results of the study, (1) Changes in coastline in 2003 - 2023 NSM accretion of 84.3 meters and abrasion of 54.2 meters, EPR accretion of 2.9 meters / year and abrasion of 2.1 meters / year. The dominant abrasion event occurred in Padang Pariaman Regency with the Nagari with the highest abrasion rate was Nagari Ketaping. (2) The results of regression analysis of the influence of geological factors and climate change on abrasion in Padang Pariaman Regency have an R Square value or Determinant Coefficient of 0.62 or 62% of lithology, rock type, rainfall and air temperature affect changes in the coastline in Padang Pariaman Regency.